2022
DOI: 10.1002/jcla.24430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D on oxidative stress and serum inflammatory factors in the patients with type 2 diabetes

Abstract: The type 2 diabetes mellitus (T2DM) is an urgent global health problem. T2DM patients are in a state of high oxidative stress and inflammation. Vitamin D and glutathione (GSH) play crucial roles in antioxidation and anti‐inflammation. However, T2DM patients have lower vitamin D and GSH levels than healthy persons. A randomized controlled trial was conducted to see the effect of the vitamin D supplementation on oxidative stress and inflammatory factors in T2DM patients. In this study, a total of 178 T2DM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
(112 reference statements)
0
8
1
Order By: Relevance
“…Type 2 diabetics may be particularly vulnerable to decreases in antioxidants and increases in inflammatory markers. One recent clinical trial in type 2 diabetics found that modest vitamin D supplementation helped to increase both vitamin D and glutathione levels, while decreasing oxidative stress and inflammation [ 317 ]. More research is required to understand how glutathione levels are implicated with both melatonin and vitamin D.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…Type 2 diabetics may be particularly vulnerable to decreases in antioxidants and increases in inflammatory markers. One recent clinical trial in type 2 diabetics found that modest vitamin D supplementation helped to increase both vitamin D and glutathione levels, while decreasing oxidative stress and inflammation [ 317 ]. More research is required to understand how glutathione levels are implicated with both melatonin and vitamin D.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%
“…On one hand, some studies showed a relationship between 25[OH]D and the alteration of GSH levels in T2DM. 32,33 While one meta-analysis showed that 25[OH]D supplementation had a beneficial effect improving most of the oxidative stress parameters among diabetic patients. 34 Furthermore, a study reported that severe 25[OH]D deficiency was accompanied by an increase in TNF-α in diabetic patients suffering from painful peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Under the condition of glucolipotoxicity, β-cell dysfunction can be triggered by multiple mechanisms, such as endoplasmic reticulum stress (ERS), oxidative stress (OS), and inflammation [10]. These factors, in turn, can contribute to glucose intolerance and insulin resistance, resulting in T2DM progression [11]. Notably, β-cells are more susceptible to damage from OS due to their weaker ability to eliminate oxidants compared to other types of cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D could regulate insulin, restore pancreatic β-cell function, and suppress cell apoptosis and oxidative stress in T2DM rat models [14]. Besides, several clinical studies show the potential of vitamin D to relieve or prevent T2DM [11,16,17]. Nevertheless, the anti-T2DM effect of vitamin D and related mechanisms remain to be further investigated.…”
Section: Introductionmentioning
confidence: 99%